Single-stage train formation in railway marshaling stations under an extended railcar-to-track assignment policy - Zhang, Siyu; Zhao, Jun; Zhang, Bojian; Zhao, Jiaxi; Peng, Qiyuan (Transportation research. Part C, Emerging technologies, 2025)
This paper studies a single-stage train formation problem in railway marshaling stations, aiming to efficiently assign railcars to classification tracks with one roll-in and one pull-out operation for ensuring the formation of outbound trains. Assigning railcars to classification tracks by blocks (block-to-track), by outbound trains (train-to-track), and by need (railcar-to-track) are three typical policies widely addressed in the literature. An extended railcar-to-track policy is investigated by combining the first and third policies, where railcars are preferentially assigned to their fixed-use classification tracks through a specified block-to-track scheme and then to other classification tracks if necessary, while re-humping and re-sorting operations are eliminated. We formulate the formation problem under this policy as a binary linear programming model with the objective of minimizing the total weighted cost required for train formation, including both the weighted roll-in cost and the weighted pull-out cost. A two-phase decomposition algorithm, which divides our model into a roll-in and a pull-out subproblem, is developed to improve the solving efficiency. For the roll-in subproblem, a novel group-indexed model is constructed to determine a railcar-to-track scheme with minimal total weighted roll-in cost and simplified pull-out cost. For the following pull-out subproblem, the objective is to determine a pull-out scheme that minimizes the total weighted pull-out cost. This subproblem is decomposed further into multiple simplified problems, each of which is formulated into a quadratic assignment model for each outbound train, enabling rapid solving times of this subproblem. Computational results on a set of realistic instances reveal that our algorithm outperforms two benchmark approaches, in which the roll-in subproblem is formulated respectively as a big-M and an arc-indexed model inspired by existing models, and an imitated empirical approach used in practice. The potential superiority of our proposed policy to the three existing policies is also numerically validated. •We address a single-stage train formation problem under an extended policy.•We formulate the problem into a binary integer linear programming model.•A two-phase decomposition algorithm is developed by exploiting the model structure.•Our best approach outperforms two benchmark approaches and one empirical approach.•The superiority of the extended policy to three existing policies is validated.